The Evolution of Project-Based Learning (PBL) Approaches in STEM Education: An Analysis of Trends and Their Impact on 21st Century Skills (2011-2021) - Gunawan Gunawan; Baiq Nabila Saufika Zainuri; Lovy Herayanti (Indonesian Journal of STEM Education, 2022)
This literature review comprehensively examines the evolution of Project-Based Learning (PBL) approaches within Science, Technology, Engineering, and Mathematics (STEM) education and their impact on 21st Century Skills from 2011 to 2021. Analyzing 40 scholarly articles, the study traces pedagogical shifts and trends in PBL implementation across diverse STEM contexts. Initial findings (2011-2015) highlighted a foundational focus on defining STEM integration and early explorations of PBL methodologies. Progressing into 2016-2021, the literature reveals a significant increase in the sophistication of PBL-STEM, marked by greater technology adoption (e.g., robotics, virtual laboratories) and explicit emphasis on fostering critical thinking, problem-solving, creativity, collaboration, and digital literacy. This review underscores a clear trend towards authentic, interdisciplinary PBL experiences designed to prepare students for real-world challenges. It concludes that PBL consistently acts as a robust pedagogical framework within STEM education, effectively cultivating essential 21st Century Skills for future academic and professional success.